Increasing pit‐planting density of rice varieties with different panicle types to improves sink characteristics and rice yield under alternate wetting and drying irrigation. Issue 1 (20th October 2021) - Jiang, Shuochen; Du, Bin; Wu, Qixia; Zhang, Haiwei; Zhu, Jianqiang
Abstract: The Chinese government regards ensuring food security and developing water‐saving agriculture as an important national strategy and that carrying out relevant research has important practical significance and production application value. A two‐year field experiment was conducted to explore the compensation potential in rice yield by using rice varieties with different panicle size under two water management regimes (conventional water management or CWM and alternate wetting and drying or AWD). The results showed that the large panicle rice variety resulted in greater yield, crop water productivity, spikelet density, dry matter accumulation and translocation, and photosynthesis. Compared with the CWM, the AWD had little effect on rice yield. However, with an appropriate planting density, the AWD achieved a greater grain yield compared with the CWM. Moreover, the AWD increased crop water productivity and the grain‐filling efficiency. The loss of spikelets under the AWD could be compensated by increasing the planting density. Although AWD reduced tillering number, it increased the photosynthetic rate, dry matter accumulation and its translocation to grain, and leaf area index. In addition, the adverse effects on rice growth and the yield caused by the AWD could be alleviated by increasing planting density of rice. Therefore, an appropriate planting density can be used to save water and maintain high grain yield of rice under alternate wetting and drying. Abstract : Increasing rice planting density can compensate for the negative impact of AWD on yield by increasing spikelets density, which may be a way to eliminate the risk of AWD reducing yield.